2014
DOI: 10.3109/08820139.2014.886261
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of human leukocyte antigen HLA-DRB1 subtypes associated to Graves’ disease in Romanian population

Abstract: The aim of this study was to identify the primary susceptibility HLA-DRB1 alleles associated with GD in Romanian population and to seek whether specific HLA-DRB1 haplotypes are associated with differences in the clinical presentation of GD at diagnosis. Molecular typing of HLA-DRB1 alleles was performed in 77 Romanian Caucasian GD patients and 445 racially matched controls. In GD patients, age, presence of eye disease, goiter grade, autoantibody status and titer, TSH, FT4, FT3, TT3 levels were recorded at diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Similarly to Asian population, there were discrepancies in the applied methods, group size and analyzed MHC classes ( 13 , 63 91 ). Most of the studies included only one MCH class, mainly class 2, while some studies included even only one gene, predominantly HLA-DRB1 ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly to Asian population, there were discrepancies in the applied methods, group size and analyzed MHC classes ( 13 , 63 91 ). Most of the studies included only one MCH class, mainly class 2, while some studies included even only one gene, predominantly HLA-DRB1 ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…DRB1*01 has been considered as a protective gene for GD in the Romanian population. The presence of DRB1*15 is regarded as a protective gene for GD, both in Romanians and Germans 28 37 . It is consistent with our conclusions that DRB1*0701 and DRB1*0101 are protective alleles for GD in Asian populations and DRB1*1502 may reduce the risk of GD although its pc-value shows no significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been proved that DRB1*03 and [10]. In a study on Romanian ethnicity, it was found that DRB1*03 and DRB1*11 gave an increased risk of developing GD [28]. The DRB1*0301 allele is the major suscepti-▶Table 3 HLA-DRB1 allele frequencies in patients with GD and control subjects.…”
Section: Differences Between Ethnic Groupsmentioning
confidence: 99%
“…(10). In Romanian population, HLA-DRB1*03 and DRB1*11 may be the primary susceptibility to thyroid disease whereas HLA-DRB1*01 and DRB1*15 seem to be protective (11). In other races like nonwhite South African blacks populations, has been found the associated of HLA-DR1 and DR3 (12).…”
Section: Statistics Analysismentioning
confidence: 96%